2017
DOI: 10.1016/j.brat.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficiency of psychological treatment using outcome feedback technology

Abstract: After adopting OF into their practice, this group of therapists attained similar clinical outcomes but within a shorter space of time and at a reduced average cost per treatment episode. We conclude that OF can improve the efficiency of stepped care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 33 publications
4
61
1
1
Order By: Relevance
“…First of all, ROM was not primarily implemented for accountability but predominantly intended as a beneficial adjunct to treatment (de Beurs, FIGURE 2 Scatterplots of bias due to selective inclusion, selective attrition, and bias due to all combined by response percentage. ROM can also lead to more efficient treatment delivery as outcome feedback may reduce treatment length (Delgadillo et al, 2017). Research has shown that ROM by itself can lead to better results (Boswell, Kraus, Miller, & Lambert, 2013), especially for patients at risk for treatment failure (Lambert, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, ROM was not primarily implemented for accountability but predominantly intended as a beneficial adjunct to treatment (de Beurs, FIGURE 2 Scatterplots of bias due to selective inclusion, selective attrition, and bias due to all combined by response percentage. ROM can also lead to more efficient treatment delivery as outcome feedback may reduce treatment length (Delgadillo et al, 2017). Research has shown that ROM by itself can lead to better results (Boswell, Kraus, Miller, & Lambert, 2013), especially for patients at risk for treatment failure (Lambert, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment failures tend to be overlooked by therapists (Hannan et al, 2005). ROM can also lead to more efficient treatment delivery as outcome feedback may reduce treatment length (Delgadillo et al, 2017). Furthermore, ROM grants patients a more active role in their own recovery (Patel, Bakken, & Ruland, 2008).…”
Section: Statistical Correction For Both Selective Sampling Mechanismmentioning
confidence: 99%
“…109,110 The Northern Improving Access to Psychological Therapies (IAPT) Practice Research Network is a collaboration of psychotherapy service providers and research institutes promoting the use of data for service provision and research. 111,112 Importantly, all IAPT services in the UK, which treat over 500,000 patients each year, collect common outcome measures at each session, consisting of short patient-completed questionnaires, providing data on therapy progression. IAPT data have already delivered insights on the utility of a clinician-support system that alerts therapists to patients who are not responding as well as expected, and ongoing work is using patient characteristics to guide treatment choice.…”
Section: Treatment Evaluationmentioning
confidence: 99%
“…There is evidence that routine outcome monitoring (ROM) has a positive influence on treatment efficacy (Lambert, ) and efficiency (Delgadillo et al., ) in mental health care. Routine measurements can be used in individual treatments by clinicians and patients to determine progress and the necessity to adapt interventions (Van, Dekker, Peen, van Aalst, & Schoevers, ), but they may also be used to evaluate the overall effectiveness of treatment programs, both within the same patient group as across diagnoses.…”
Section: Introductionmentioning
confidence: 99%